2021
DOI: 10.21203/rs.3.rs-170495/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigation of Three Drugs With Neuroregenerative Effects on Inferior Alveolar Nerve Injury in Rats

Abstract: PurposeNerve injuries formed during oral and maxillofacial surgical operations occur usually by crush or tension-type damages rather than incisions or ruptures. Such nerve injuries can be treated by providing regeneration with pharmacological agents without surgical intervention. The aim of this study was to determine and compare the effects of dexamethasone, B vitamin complex, and nerve growth factor on peripheral nerve regeneration with a local application on the inferior alveolar nerve. Methods Twenty-four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Furthermore, it is recommended that steroid therapy is prescribed (step down 5‐day course of Prednisone Oral 50–40–30–20–10 mg) at the earliest identification of a traumatic IAN injury 26 . This is supported by various experimental studies which have shown steroids play an important role in reducing neuroinflammation, which can lead to accelerated functional recovery of nerves after trauma 27,28 . In severe cases, such as the one described, further treatment may involve a nerve graft 29 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, it is recommended that steroid therapy is prescribed (step down 5‐day course of Prednisone Oral 50–40–30–20–10 mg) at the earliest identification of a traumatic IAN injury 26 . This is supported by various experimental studies which have shown steroids play an important role in reducing neuroinflammation, which can lead to accelerated functional recovery of nerves after trauma 27,28 . In severe cases, such as the one described, further treatment may involve a nerve graft 29 …”
Section: Discussionmentioning
confidence: 96%
“…26 This is supported by various experimental studies which have shown steroids play an important role in reducing neuroinflammation, which can lead to accelerated functional recovery of nerves after trauma. 27,28 In severe cases, such as the one described, further treatment may involve a nerve graft. 29…”
Section: Discussionmentioning
confidence: 99%